Analisis Data Tersensor Kanan dengan Metode Cox Proportional Hazard Model - La Ode Nashar; Asriadi Asriadi; Dewi Rahmawaty Isa (UIN Imam Bonjol Padang, 2022)
In time series data research, it is often encountered the problem of lack of available time and budget. So often found the presence of censored data. Censored data can be analyzed using the partial likelihood method. However, other obstacles will arise if the processed data contains ties. So it is necessary to use other methods that can overcome the co-occurrence. In this study, the Breslow method is used to estimate the censored data due to joint events. This method is applied to the case of patients with burns. The variables used are the method of treatment, gender, race and type of burn. The results of the analysis showed that race did not give a significant difference to the incidence of cutting burned organs. While the other three variables showed significant differences at the 95% confidence level. The results of the analysis using the Cox proportional hazard method showed that patients treated with the body cleansing method had 17% greater risk of cutting than those treated with the body routhine bathing.